2021
DOI: 10.48550/arxiv.2107.14468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primes between consecutive powers

Abstract: This paper updates two explicit estimates for primes between consecutive powers. We find at least one prime between n 3 and (n + 1) 3 for all n ≥ exp(exp(32.9)), and at least one prime in (n 296 , (n + 1) 296 ) for all positive n. These results are in part obtained with a explicit version of Goldston's (1983) estimate for the error in the Riemann-von Mangoldt explicit formula.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…where G(x, h) = (x + log 1−ω (x + h) + x log 1−ω x, and M , ω, and x M can be taken from Table 5. With (5.1), similar working to that of Section 4 in [CH21] gives a condition for primes between n m and (n + 1) m . The only change we make is setting T = x µ /1.8, for any µ ∈ (0, 1), instead of 3 T = x µ .…”
Section: Application: Primes Between Consecutive Powersmentioning
confidence: 96%
See 4 more Smart Citations
“…where G(x, h) = (x + log 1−ω (x + h) + x log 1−ω x, and M , ω, and x M can be taken from Table 5. With (5.1), similar working to that of Section 4 in [CH21] gives a condition for primes between n m and (n + 1) m . The only change we make is setting T = x µ /1.8, for any µ ∈ (0, 1), instead of 3 T = x µ .…”
Section: Application: Primes Between Consecutive Powersmentioning
confidence: 96%
“…To give a short-interval result for all positive n, we need to consider higher powers. In [CH21] it was shown that there are always primes between consecutive m th powers for m = 180. The proof used a number of estimates relating to the error in the prime number theorem, including an explicit version of Goldston's estimate for ψ(x) [Gol83].…”
Section: Application: Primes Between Consecutive Powersmentioning
confidence: 99%
See 3 more Smart Citations